2020
DOI: 10.1002/clc.23487
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with valsartan and fluvastatin to delay disease progression in nonpermanent atrial fibrillation with hypertension: A clinical trial

Abstract: Background: Atrial fibrillation (AF) is a complex cardiac arrhythmia in clinical practice with increasing incidence. However, the effects of statins on patients with AF are not quite clear. Hypothesis: To investigate the protective effect of calcium channel blocker (CCB) and valsartan combined fluvastatin on hypertension (HTN) patients with nonpermanent AF. Methods: In three and a half years, 189 cases of patients diagnosed as HTN combining nonpermanent AF by eight medical centers, were recruited and randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Majority of our study participants were either using valsartan or losartan potassium and this finding of our study confirms prior evidence in this respect as shown by multiple studies. 23,24 The mechanism by which ARBs prevent atrial fibrillation is wellestablished and is related to the blockade of effects of the renin-angiotensin system through the electrical and structural remodeling of atria. 25 Here it is worth mentioning that although amiodarone is one of the most commonly used antiarrhythmic drug and is known to decrease the occurrence of atrial tachyarrhythmia but in our study it was not associated with reduction of AHRE episodes, this may be due to lesser number of patients using amiodarone as patients with known atrial fibrillation were excluded from the study Our study included patients with Dual chamber PPM and ICDs as well as patients with CRTD and CRTP whereas in prior studies only a population with pacemakers was studied.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of our study participants were either using valsartan or losartan potassium and this finding of our study confirms prior evidence in this respect as shown by multiple studies. 23,24 The mechanism by which ARBs prevent atrial fibrillation is wellestablished and is related to the blockade of effects of the renin-angiotensin system through the electrical and structural remodeling of atria. 25 Here it is worth mentioning that although amiodarone is one of the most commonly used antiarrhythmic drug and is known to decrease the occurrence of atrial tachyarrhythmia but in our study it was not associated with reduction of AHRE episodes, this may be due to lesser number of patients using amiodarone as patients with known atrial fibrillation were excluded from the study Our study included patients with Dual chamber PPM and ICDs as well as patients with CRTD and CRTP whereas in prior studies only a population with pacemakers was studied.…”
Section: Discussionmentioning
confidence: 99%
“…Selected clinical trials regarding the beneficial and pleiotropic effects of statins are presented in Table 2. reduction of LDL cholesterol level/NCT03242499 [111], NCT04359823 [112] the effect on synaptic plasticity, cognitive function, and attention in patients with RASopathies/NCT03504501 [113] improvement in the treatment of diffuse superficial actinic porokeratosis/NCT04359823 [112] modulation of cortical inhibition in neurofibromatosis type 1 (NF1)/NCT03826940 [114] reduction of motor symptoms in patients with early-stage Parkinson's/NCT03242499 [111] pravastatin reduction of LDL cholesterol level/ACTRN12616000535471 [115] prevention of pre-eclampsia in pregnant women/NCT01717586 [116] biomarker for monitoring the clinical benefit of statin treatment in secondary prevention/ ACTRN12616000535471 [115] prevention of the occurrence of atherothrombotic brain infarction in noncardioembolic infarction patients/NCT00361530 [117] reducing the incidence of lacunar stroke/NCT00221104 [118] reduction in levels of lipoprotein subclasses/NCT03073018 [119] reduction of vascular inflammation in non-cardiogenic ischemic stroke/NCT00361699 [120] simvastatin inhibition of 3-hydroxy-3-methyl-glutaryl-CoA reductase/ NCT00529139 [121] reduction in serum LDL concentration/NCT00939822 [122], NCT01061671 [123] activation of PI3K-kinase/NCT00676897 [121] positive effect on emotions/NCT04652089 [124] improved survival in ever-smokers with extensive disease (ED)-small cell lung cancer (SCLC)/NCT01441349 [125] reductions in total cholesterol, lipoprotein, and triglycerides observed in children with type 1 diabetes mellitus/NCT03660293 [126] anti-inflammatory and neuroprotective effects/NCT01999309 [127] prevention of decompensation in patients with compensated cirrhosis/NCT03654053 [128] Type II-synthetically derived statins fluvastatin reduction in blood lipid levels/ ChiCTR-TRC-12002642 [129] decrease in LDL-level/NCT00421005 [130] decrease of inflammatory index, ultrasonic index and electrocardiographic measurement results in atrial fibrillation/ChiCTR-TRC-12002642 [129] normalization of bilirubin levels and reduced blood ...…”
Section: Cerivastatinmentioning
confidence: 99%
“…More recently, data from the ESC-EHRA EORP registry found hypertension to be a univariate predictor of atrial fibrillation recurrence, although this lost significance following adjustment [42]. Findings from a German registry of persistent atrial fibrillation patients showed that hypertension was also a significant predictor for rehospitalization, dyspnoea and angina after atrial fibrillation ablation [48] (Table 2) [13,[84][85][86][87][88][89][90][91][92][93][94][95][96][97].…”
Section: Secondary Prevention In Atrial Fibrillation: Implications Fo...mentioning
confidence: 99%